2010
DOI: 10.1111/j.1751-7893.2010.00170.x
|View full text |Cite
|
Sign up to set email alerts
|

What factors are related to delayed treatment in individuals at high risk for psychosis?

Abstract: These findings suggest that high-risk subjects frequently received delayed treatment despite symptomatic distress and functional impairment. No direct evidence supporting the delayed effect of the DUAPS on baseline psychopathology was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 36 publications
(49 reference statements)
2
19
0
Order By: Relevance
“…Based on these or similar criteria, studies with followup times ranging from 1 to 9.6 years report a transition rate to full psychotic syndromes of 9 -54% (Amminger et al, 2006;Olsen and Rosenbaum, 2006;Chung et al, 2010). A 2-year follow-up study of 292 help-seeking individuals found a transition rate of 16%, which is considerably lower than the rates reported in earlier studies (over 40%) (Yung et al, 2008).…”
Section: Transition From Health To Psychosis: the Ultra-high-risk Statementioning
confidence: 86%
“…Based on these or similar criteria, studies with followup times ranging from 1 to 9.6 years report a transition rate to full psychotic syndromes of 9 -54% (Amminger et al, 2006;Olsen and Rosenbaum, 2006;Chung et al, 2010). A 2-year follow-up study of 292 help-seeking individuals found a transition rate of 16%, which is considerably lower than the rates reported in earlier studies (over 40%) (Yung et al, 2008).…”
Section: Transition From Health To Psychosis: the Ultra-high-risk Statementioning
confidence: 86%
“…Global functioning did not significantly differ between patients with long (N1 year) and short (b1 year) durations of untreated attenuated psychotic symptoms (Chung et al, 2010). However, a longer duration of prodromal symptoms was associated with increased impairment on the 'Interpersonal behaviour' and 'Prosocial activities' subscales of the Social Functioning Scale (Shim et al, 2008a).…”
Section: Duration Of Symptomsmentioning
confidence: 97%
“…Specifically, the risk for psychosis onset rises dramatically following age 13, and increases with each year of age through adolescence (de Girolamo et al, 2012; Thorup at al., 2007). In clinical high risk (CHR) samples, the prodromal syndrome shows a similar trend, and appears to predate psychosis onset by about a year (Chung et al, 2010). …”
Section: Introductionmentioning
confidence: 99%